Efektifitas Edukasi Kesehatan melalui whatsapp terhadap Peningkatan Pengetahuan dan Sikap Penderita TB dalam Pencegahan Penularan TB Paru di UPTD Puskesmas Tapung II - Salmiyenti yenti; Mitra Mitra; Zainal Abidin; Novita Rany; Emy Leonita (LPPM Hang Tuah Pekanbaru, 2023)
Tuberculosis is the biggest health problem in the world, after HIV (Human Immunodeficiency Virus) so it must be treated seriously. The implementation of media health promotion is one of the important things, this is related to health promotion goals and materials. The purpose of the study was to determine the effectiveness of health education through WhatsApp on the knowledge and attitudes of TB patients in preventing pulmonary TB transmission at the UPTD of the Tapung II Health Center in 2021. The research location was in the UPTD of the Tapung II Health Center. Type The research method is a quantitative study using a quasi-experimental design with control or pre and post-test. The research sample consisted of 30 people, the sampling method was using purposive sampling, dividing the entire sample into 2 groups, namely group I (experimental) and group II (control). Data analysis was carried out using univariate, bivariate, and multivariate methods. It was found that there is a difference in knowledge before and after the intervention through the WhatsApp media with a p-value of 0.000 (p-value <0.05). There is a difference in attitude before and after the intervention through Whatsapp media with a p-value of 0.000 (p-value <0.05). The conclusion of this study is the effectiveness of health education via WhatsApp in increasing the knowledge and attitudes of TB sufferers in the prevention of pulmonary TB transmission. It is recommended to the person in charge of the TB program at the Puskesmas to always be active in TB consultations via WhatsApp, and for the local government, especially the Kampar District Health Office, to be able to design better health promotion strategies in reducing TB cases through TB prevention programs.